DETERMINANTS OF UKRAINIAN ECONOMIC AND FOOD SECURITY DEVELOPMENT UNDER THE CONDITIONS OF MARTIAL LAW - Lidiia Shynkaruk; Maryna Dielini; Tetiana Vlasenko; Denys Svyrydenko; Volodymyr Lagodiienko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The aim of the study is to find out the determinants of economic development and food security in Ukraine under martial law. The relevance of this topic is determined by the agricultural orientation of the Ukrainian economy and the problems of exporting under war conditions, which can lead to famine all over the world and a decrease in cash receipts in the budget of Ukraine. The main results of the research showed that until now Ukraine was focused on the production of law value-added goods. In addition, a significant decrease in GDP during the war and the study of the experience of the Second World War made it possible to assume that the economic decline was caused not only by war factors but also by structural imbalance and the raw nature of the economy. The agro-industrial complex of our country, on the one hand, can ensure food security, both within the country and in the world, but taking into account recent events, this is not always possible. It is worth noting that russia increased wheat exports, and Ukraine, on the contrary, was forced to reduce it. Also, a ban on the export of Ukrainian agricultural products in some countries of the EU until June 5, 2023, caused a great resonance in society due to negative economic consequences. It was proposed to extend this ban, which cannot have a positive effect on the economy of our country. Taking this into consideration, it is necessary to change the entire economic course of the country, which should take into account national economic interests, security determinants, reduce dependence on external factors, and balance the structure of the economy. The export of agricultural products should be carried out not only due to the interests of the EU but also the national interests of Ukraine.